2007
DOI: 10.1080/09578810701289212
|View full text |Cite
|
Sign up to set email alerts
|

Migration as a Household Decision: What are the Roles of Income Differences? Insights from the Volta Basin of Ghana

Abstract: This paper examines the determinants of migration decision with a special emphasis on the role of income differences. As migrants are not a random part of the population, the migration equation is corrected for selectivity bias using the Heckman procedure. The data for this study is collected under a Common Sampling Frame approach, which resulted in a wide variety of data sets. Empirical results show the statistically significant effects of income differentials on households' decisions to participate in migrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 30 publications
5
26
0
Order By: Relevance
“…Although the reason for such an occurrence was not obvious in Addawen (2013), Luginaah and colleagues in an earlier study (2009) found that poor transportation and communication networks were affecting the frequency of remitting to the region. Therefore, remittances as a diversification strategy may only minimize the negative impacts of shocks on poor households by smoothing consumption in the short run (Tsegai, 2007). Several studies have observed the reliance of households on a combination of remittances and other strategies by poor households to meet their food needs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the reason for such an occurrence was not obvious in Addawen (2013), Luginaah and colleagues in an earlier study (2009) found that poor transportation and communication networks were affecting the frequency of remitting to the region. Therefore, remittances as a diversification strategy may only minimize the negative impacts of shocks on poor households by smoothing consumption in the short run (Tsegai, 2007). Several studies have observed the reliance of households on a combination of remittances and other strategies by poor households to meet their food needs.…”
Section: Discussionmentioning
confidence: 99%
“…However, drastic changes in the agro-ecological environment over at least the last three decades have had dire consequences on agricultural livelihoods ( Van der Geest et al, 2010). Agriculture employs over a third of the labour force in the UWR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their empirical analysis is largely descriptive, though, and they do not seek to derive a measure of perceived riskiness of migration (or remaining in Hong Kong). Finally, it is worth noting that Tsegai (2007) emphasizes the riskreducing role of education in exploring migration within Ghana. In summary, there is ample reason to believe that uncertainty is important in the migration decision, but there have been few attempts at empirical verification.…”
Section: Previous Studiesmentioning
confidence: 99%